Participation in Florida Growth Management Decisions - Roy Carriker (EDIS)
FE644, a 2-page fact sheet by Roy Carriker, introduces members of the public to the subject of public participation in official growth management decision processes. Published by the UF Department of Food and Resource Economics, August 2006.